Strategi Compliance Gaining dalam Dakwah Larangan Berpacaran pada Keluarga Islam (Studi Kasus pada Keluarga dari Ormas-Ormas Islam di Kota Yogyakarta) - Syahril Taufiq Hidayat (Alhadharah: Jurnal Ilmu Dakwah, 2024)
This research focuses on dating behavior that begins to imitate western culture and is characterized by promiscuity, even becoming a trend among today's teenagers. This is a defiance for Islamic families because it can lead to adultery. Therefore, communication strategies are needed that can prevent children from dating behavior in Islamic families. This research adopts the five main strategies of gaining compliance from Marwell & Schmitt's (1967) research implemented in dakwah. This research uses a qualitative case study method with data collection techniques through non-participant observation and in-depth interviews by probing and crosschecking. The results showed that in the first strategy, only one family used the strategy of giving gifts. The gifts given are in the form of a simple meal together outside the home as a form of compliance with parents. While other parents use the command strategy; The second strategy, parents provide threats or prohibitions on the use of gadgets, social restrictions, etc.; The third strategy, parental expertise is shown through delivery based on religious arguments, sexual education, and an overview of the negative or positive effects of dating, and parents' dating traditions. This strategy is in line with the da'wah method of al-Mau'idzah al-Hasanah; The fourth strategy, parents educate children a sense of sin if they date as a form of impersonal commitment; The fifth strategy, personal commitment is shown through the status as a child to always be devoted (obedient) to parents.